2020
DOI: 10.1002/ccr3.3419
|View full text |Cite
|
Sign up to set email alerts
|

Silicosis in a paint‐production worker: Study of a lung histological specimen with scanning electron microscopy—Energy dispersive X‐ray spectrometer

Abstract: BACKGROUND We reported an uncommon case of silicosis in a worker involved for 25 years in the production of paints (water-based paints and quartz paints for the building industry). The etiology was confirmed by investigating a lung histological specimen with a scanning electron microscope equipped with an energy dispersive X-ray spectrometer. Crystalline silica is a mineral widely found on earth as part of sand, rock, and mineral ores such as quartz. The most common free crystalline forms of silica in workplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, the rapid improvement of the lung lesions during steroid therapy goes against a diagnosis of silicosis, as this is not typically indicative of pneumoconiosis. Indeed, such a response to steroid treatment may occur in sarcoidosis, whereas silicosis results in irreversible lung damage [17,18]. Moreover, no silicotic nodules or signs of fibrosis were found in the patient's biopsy specimen, and the micronodular shadow on the chest CT was not typical of silicosis caused by 18 years of exposure to silica.…”
Section: Discussionmentioning
confidence: 93%
“…However, the rapid improvement of the lung lesions during steroid therapy goes against a diagnosis of silicosis, as this is not typically indicative of pneumoconiosis. Indeed, such a response to steroid treatment may occur in sarcoidosis, whereas silicosis results in irreversible lung damage [17,18]. Moreover, no silicotic nodules or signs of fibrosis were found in the patient's biopsy specimen, and the micronodular shadow on the chest CT was not typical of silicosis caused by 18 years of exposure to silica.…”
Section: Discussionmentioning
confidence: 93%
“…Controversially, we acknowledge that the rapid improvement of the lung lesions on steroid therapy typically should not indicate a diagnosis of silicosis, because pneumoconioses generally lead to irreversible lung damage. (3,4) In the literature, there is a case-report of silicosis that responded to steroid therapy, but in the case of our patient, we decided to consider this as a feature of sarcoidosis, especially in view of the concomitant calcitriol-mediated hypercalcemia. (5) Sarcoidosis is a systemic disease of unclear etiology, whereas SLR is an immune-mediated response to certain antigens, which relate to localized clinical features and do not ful ll the sarcoidosis criteria.…”
Section: Discussion Conclusionmentioning
confidence: 92%
“…It is done considering the costs incurred due to health problems and work accidents caused by the work environment are significant with the harm it causes (ILO, 2008). The exposure can also develop into autoimmune disorders, chronic kidney disease, and others (Baron et al, 2002;De Maria et al, 2020). Studies in China showed that 10 million workers contracted silicosis, with 5000 reported deaths (Natural Stone Institute, 2018).…”
Section: Introductionmentioning
confidence: 99%